Pendidikan Islam Pra-Kemerdekaan: Difusi, Akulturasi, dan Modernisasi dalam Membangun Identitas Nusantara - Attarikhul Kabir (Islamic Education, 2025)
This study aims to explore the historical trajectory of Islamic civilization in the Indonesian archipelago prior to independence, focusing on its role in shaping socio-political, cultural, and religious life. Using a qualitative historical approach through literature review and content analysis of classical and modern sources, the research traces the Islamization process carried out through trade, education, intermarriage, and da‘wah activities. The analysis engages competing theories on the arrival of Islam and highlights the dynamic adaptation of Islamic values within local traditions. The results show that the establishment of Islamic kingdoms, the spread of pesantren as centers of learning, and the rise of organizations such as Muhammadiyah, Nahdlatul Ulama, Persis, and Masyumi demonstrate Islam’s central role in building governance structures, knowledge systems, and collective identity. More than a religion, Islam functioned as a transformative civilizational force that strengthened resilience against colonial pressures while providing cultural continuity. This study contributes to the understanding of how Islamic civilization before independence laid institutional and ideological foundations for modern Indonesian society. The novelty lies in its synthesis of diverse historical perspectives to reveal Islam’s integrative and enduring role as both a spiritual and socio-political catalyst in the archipelago.